2000
DOI: 10.2169/internalmedicine.39.123
|View full text |Cite
|
Sign up to set email alerts
|

The Sera from GM1 Ganglioside Antibody Positive Patients with Guillain-Barre Syndrome or Chronic Inflammatory Demyelinating Polyneuropathy Blocks Na+ Currents in Rat Single Myelinated Nerve Fibers.

Abstract: Objective To determine the possible role of anti-GMl ganglioside antisera from patients with Gullain-Barre syndrome (GBS) or chronic inflammatory demyelinating polyneuropathy (CIDP) in the development of nerve dysfunction.Methods The effect of the anti-GMl antibody positive antisera obtained from 4 GBS patients and 1 CIDP patient on membranepotential and ionic currents in rat single myelinated nerve fibers was investigated using the voltage clamp technique and compared with that of the anti-GMl negative antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 15 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…During a minor infectious disease these lymphocytes become activated upon encountering microbial epitopes. The hallmark finding that microbial epitopes can resemble endogenous peripheral nerve antigens has been termed “molecular mimicry.”133, 134, 136 Autoreactive T lymphocytes stimulate B cells to produce autoantibodies, which in turn can block nerve conduction,119, 128 activate complement,102, 115 and facilitate a macrophage attack in the peripheral nerve. Activated T cells transgress the blood–nerve barrier and provoke local inflammation by proinflammatory cytokines 54.…”
mentioning
confidence: 99%
“…During a minor infectious disease these lymphocytes become activated upon encountering microbial epitopes. The hallmark finding that microbial epitopes can resemble endogenous peripheral nerve antigens has been termed “molecular mimicry.”133, 134, 136 Autoreactive T lymphocytes stimulate B cells to produce autoantibodies, which in turn can block nerve conduction,119, 128 activate complement,102, 115 and facilitate a macrophage attack in the peripheral nerve. Activated T cells transgress the blood–nerve barrier and provoke local inflammation by proinflammatory cytokines 54.…”
mentioning
confidence: 99%
“…Based upon the waveform changes of action potential, other ion channels, such as potassium (K + ) channels, might also be involved in CTX‐B‐mediated response, but it was unclear whether it was directly caused by CTX‐B binding or secondary to the Na + channel modulation. Others showed that GM1 ganglioside antibody significantly changed the action potential waveform and reduced Na + currents without the effect on K + channel currents (Takigawa et al. 2000), suggesting that the decrease in K + channel activity was a secondary response to Na + channel disruption/modulation‐mediated by CTX‐B.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this modification of receptor function in these cases has been linked to disease severity (see, e.g., Rogers et al, 1996;Gahring and Rogers, 1998). Other receptors expressed on CNS cells can also be targets of autoantibodies that alter their normal function, including voltage-gated calcium channels in Lambert-Eaton syndrome (and in some cases of sporadic amyotrophic lateral sclerosis), potassium channels as in Isaacs' syndrome (neuromyotonia), and sodium channels in some patients with acute inflammatory demyelinating polyneuropathy (AIDP) and Guillain-Barré syndrome (for examples, see De Aizpurua et al, 1988;Lennon et al, 1995;Lang and Vincent, 1996;Smith et al, 1992Smith et al, , 1996Dinkel et al, 1998;Houzen et al, 1998;Offen et al, 1998;Pinto et al, 1998;Nagado et al, 1999;Archelos and Hartung, 2000;Takamori et al, 2000;Takigawa et al, 2000;Waterman et al, 2000). Autoantibodies that alter the function of glutamatergic metabotropic receptors have also been described from the serum of patients with paraneoplastic disease (Sillevis Smitt et al, 2000).…”
Section: Discussionmentioning
confidence: 99%